The C allele of the AGT Met235Thr polymorphism is associated with power sports performance - Gomez-Gallego, F.; Santiago, C.; Gonzalez-Freire, M.; Yvert, T.; Muniesa, C. A.; Serratosa, L.; Altmäe, S.; Ruiz, J. R.; Lucia, A. (Applied Physiology, Nutrition, and Metabolism, 2009)
Whether the Met235Thr (rs699) variation in the angiotensinogen (AGT) gene, encoding a threonine instead of a methionine in codon 235 of the mature protein, is associated with athletic performance remains to be elucidated. We compared the genotype and allele frequencies for the AGT Met235Thr variation (rs699) in 119 nonathletic controls, 100 world-class endurance athletes (professional cyclists, Olympic-class runners), and 63 power athletes (top-level jumpers, throwers, sprinters). Participants were all males and from the same descent (Caucasian) for =3 generations. The proportion of the CC genotype was significantly higher in the power group (34.9%) than in either the control (16%) or the endurance group (16%) (p = 0.008 and p = 0.005, respectively). The odds ratio (95% CI) of being a power athlete if the subject has a CC genotype was 1.681 (1.176-2.401), compared with the control group. In summary, the C allele of the AGT Met235Thr polymorphism might favour power sports performance. Although more research is needed, this could be attributed to the higher activity of angiotensin II, a skeletal muscle growth factor.